Comparison of Acoustocerebrography Measurement and Magnetic Resonance Imaging Methods in the Assessment of White Matter Lesions in Patients with Atrial Fibrillation - Wioletta DOBKOWSKA-CHUDON; Mirosław WROBEL; Emilia FRANKOWSKA; Arkadiusz ZEGADLO; Andrzej KRUPIENICZ; Andrzej NOWICKI; Robert OLSZEWSKI (Archives of Acoustics)
The brain is subject to damage, due to ageing, physiological processes and/or disease. Some of the damage is acute in nature, such as strokes; some is more subtle, like white matter lesions. White matter lesions or hyperintensities (WMH) can be one of the first signs of micro brain damage. We implemented the Acoustocerebrography (ACG) as an easy to use method designed to capture differing states of human brain tissue and the respective changes.